Penerapan Self-Help Skill untuk Membentuk Kemandirian Siswa Kelas Rendah Sekolah Dasar di Kabupaten Grobogan - Puspadenty Arningtyas Anggraeny (Indonesian Journal of Elementary Education and Teaching Innovation, 2026)
Many lower-grade elementary school students have not optimally developed self-help skills, the ability to independently perform daily activities such as changing clothes, eating, and maintaining personal hygiene. This study examines how these skills are practiced among ﬁrst- to third-grade students in six public and private elementary schools in Grobogan Regency, a stage when children are expected to take over routines previously assisted by adults. A qualitative descriptive approach was used, with data collected through in-depth interviews, classroom observations, and document analysis involving 12 class teachers, six principals, and 30 parents. Only two of the six schools had a structured self-help skill program; the rest relied on incidental guidance from teachers. Where structured practices were in place, students adapted faster, showed more conﬁdence, and were better prepared to learn. Inconsistent practices between home and school created a double burden for children caught between diﬀerent sets of expectations. Three categories of barriers were found: limited parental understanding of age-appropriate independence, constraints on teacher time and training, and the absence of a systematic school program. Good practices observed in the ﬁeld included weekly self-help routines and a home-school communication notebook, both supported by principal leadership that encouraged collaboration among teachers and parents. These ﬁndings suggest that self-help skill development depends as much on coordination between schools and families as on classroom instruction. The study recommends including self-help skill indicators in the grades I-III curriculum, strengthening teacher preparation, and building more structured school- parent collaboration.